Evaluation of an Agroforestry System: The Growth of 14-Month-Old Solomon Sengon (Falcataria moluccana) and Rice (Oryza sativa) - Nurheni Wijayanto; Sahida Haurani Tsaniya (Jurnal Sylva Lestari, 2022)
Solomon sengon is a provenance of sengon that grows faster than other local sengon species. The species is often cultivated in an agroforestry system, which can be combined with rice as the staple food in Indonesia. Competition between those two components to obtain the sunlight and nutrients is getting higher as sengon grows. LIPI and IPB have discovered several rice varieties. However, there has not been much research done on agroforestry between Solomon sengon (Falcataria moluccana) and rice (Oryza sativa) varieties. This study aimed to analyze the growth of Solomon sengon at 14 months old and the productivity of several rice varieties. This study used a completely randomized factorial design with two factors, namely the tree spacing factor of Solomon sengon type F2 (1.5 m × 3 m and 1.5 m × 1.5 m) and the factor of upland rice varieties (LIPI Go 1, LIPI Go 2, and IPB 9G) also lowland rice (IPB 3S). Parameters observed were sengon growth and rice productivity. Data were analyzed statistically using the analysis of variance (ANOVA) test and the Duncan test with a confidence interval of 95%. The results showed that the 14-month-old Solomon sengon with a tree spacing of 1.5 m × 3 m has a higher diameter, height, and canopy area than a tree spacing of 1.5 m × 1.5 m. The rice varieties of LIPI Go 1, LIPI Go 2, IPB 9G, and IPB 3S planted under 14-month-old sengon with a tree spacing of 1.5 m × 3 m have higher productivity than rice planted under sengon with a tree spacing of 1.5 m × 1.5 m. Rice varieties significantly affected several rice growth parameters. IPB 3S has the optimum growth and production in this study. IPB 3S is the variety with the highest number of tillers per clump and the highest number of productive tillers per clump. IPB 3S is the variety with the highest number of tillers per clump and the highest number of productive tillers per clump. Keywords: agroforestry, rice, Solomon sengon, tree spacing